Factors Affecting Internationalization of Indonesia Franchise Companies - Halim, Erwin (Bina Nusantara University, 2013)
Franchise is one of successful business strategies in business expansion. Franchise format has been already adopted in all countries. The success is proven in the world and also in Indonesia. Franchise system can be implemented not only in franchisor country but also in other countries. The spirit of internalization is not only because of market saturated, but also to increase reputation of franchise companies and to follow competitors or customers. Important thing discussed in this research is the franchise life-cycle, franchise growth model, and franchise companiesâ profile. Â It is found that the Indonesia franchise companies are in the introduction stage. The stage in life-cycle shows its reputation. This study used literature review as methodology, and the purpose of this study is to give a big picture for Indonesia franchise companies to make internationalization. There are some Indonesia franchise business profiles in the discussion part. The factors affecting franchise internationalization were analyzed by PESTEL analysis. Some strategies should be prepared in making decision to go international. Â At the end, there are some recommendations and future research relating to internationalize franchise business.